Pengaruh Sistem Perkawinan Islam terhadap Sistem Hukum Perkawinan Masyarakat - Sugiatminingsih, Sugiatminingsih (UIN Maulana Malik Ibrahim Malang, 2005)
Islamic marriage law before being legalized as Marriage Constitution, the norms related to marriage system (marriage procedures) in Islam has actually been long applied in Moslem society. Even, since Islam first came and established Moslem community. Pancasila is the basic principles of Indonesia and the majority of Indonesian people are Moslem. So, in order to develop national constitution, Islamic law has a huge chance to be the only main source needed in that development of the national constitution. This article states the history of law constitution in the first era of Islam in Indonesia and also the influence of culture and mazhab. Furthermore, Islamic marriage system is also presented. The compilation of Islamic law in aiming for uniformity in religious court becomes the guidance for the judges in taking decisions. Therefore, the guarantee on the equality of unity and law certainty can be realized. Hukum Perkawinan Islam sebelum disahkan sebagai Undang-Undang Perkawinan, norma yang berhubungan dengan system perkawinan (tata cara perkawinan) secara Islam sebenarnya telah lama berlaku dalam masyarakat Islam. Bahkan sejak pertama kali agama Islam masuk dan membentuk komunitas Islam. Pancasila ialah dasar negara Indonesia dan sebagian besar penduduk Indonesia beragama Islam. Maka, dalam rangka pembinaan Hukum Nasional, hukum Islam mempunyai peluang yang sangat besar untuk masuk sebagai salah satu bahan pokok yang sangat diperlukan dalam pembinaan hukum nasional tersebut. Artikel ini memaparkan sejarah undang-undang di awal masuknya Islam ke Indonesia serta budaya dan mazhab yang mempengaruhinya. Lebih khusus lagi, sistem perkawinan Islam juga menjadi pembahasan. Adanya kompilasi hukum Islam yang bertujuan untuk keseragaman dalam peradilan agama, menjadi acuan para hakim dalam menentukan keputusan. Sehingga, jaminan akan adanya persamaan kesatuan dan kepastian hukum bisa terwujud.